A cotyledonoid dissecting leiomyoma with an intravascular component and adenomyosis accompanied with possible multiple lung metastases: A case report - Jumpei Kashima; Akiko Tonooka; Ayumi Taguchi; Nobuaki Funata; Toshiharu Yasugi; Tsunekazu Hishima (Elsevier, 2019)
A cotyledonoid dissecting leiomyoma (CDL) is a rare variant of a uterine smooth muscle cell tumor and is characterized by intramural and extrauterine growth patterns with dissection of the uterine myometrium.We encountered a case of a CDL with multiple lung nodules. Computed tomographic and magnetic resonance imaging results revealed the presence of a multilobulated abdominal mass with cystic components contiguous to the uterine corpus and well-demarcated nodules measuring ≤2 cm in diameter in the bilateral lungs. Simple hysterectomy and bilateral salpingo-oophorectomy were performed.Macroscopically, a placenta-like tumor protruded from the medial fundus of the uterine corpus toward the intraluminal and peritoneal cavities. Histologically, the tumor was composed of neoplastic spindle cells with hyalinized degeneration and vascular proliferation. Endometrial glands with stroma and vascular invasion were also noted.This is the first report of a CDL with possible metastasis. Histological features, including intravascular growth, may predict the aggressive behavior of this tumor. Keywords: Adenomyosis, Leiomyoma, Smooth muscle tumor